PEMANFAATAN APLIKASI GIS DALAM PENATAAN RUANG - Amiany, Amiany (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2017)
Spatial planning has an important role in the implementation of development in order toachieve a sustainable development that is the form of factual contribution in the sustainabledevelopment of regional and city, thus justice and welfare to all Indonesian can be achieved.The application of GIS is not everything in spatial development. However, the spatial planningwill be easier by the assistance of GIS as a tool to collect spatial data and analysis. GIS applicationbecomes important since spatial development manages spatial and non-spatial data.GIS uses as a tool to analysis the spatial data based on desired accuracy. It allows themonitoring and evaluation of the implementation of spatial planning. It uses to support decisionmaking in the implementation of development.